(untitled) (Journal of Engineering, 2024)
Airborne radioactive particulates (for both indoor and outdoor air), in Al-Jaderiya region (Baghdad), have been collected to measure the concentration of Radon-222 daughter products of gamma ray emission (214Pb, 214Bi and 218Po) and hence calculate the concentration of Radon-222. 24 samples were analyzed (12 indoor and others outdoor), using gamma ray spectrometric system based on a High purity Germanium detector (HpGe) of (40%) efficiency. The average concentrations of Radon-222, were found to be (93.7 Bq/m3) and (18.9 Bq/m3), in indoor and outdoor air respectively. The comparison of these concentrations with some internationally typical values has showed that the concentrations of Radon-222 are higher in outdoor air of the area of study compared with many regions in USA and other countries. On the contrary, the concentrations of Radon-222 in indoor air of the area of study are less than those in many European countries.